Monitoring biophysical and socioeconomic impacts of CSA practices at Doyogena and Basona Climate-Smart Landscapes, Ethiopia - Nigussie, Abebe; Ambaw, Gebermedihin; Tesfaye, Abonesh (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2021)
This activity was conducted to determine climate-smart agricultural practices’ biophysical and socioeconomic impacts over the last 12 months, using the Doyogena (Southern Ethiopia) and Basona (North Ethiopia) climate-smart landscapes as a case study. More specifically, this activity addressed if CSA practices (i) guarantee farmers resilience to climate change; (ii) increase food productivity and household income; and (iii) prevent gender-related bias (i.e., improving women’s participation in decisions, access/control over resources). From each site, 200 adopters (i.e., farmers who practice the above-mentioned practices) and 200 non-adopters (i.e., farmers` as usual practices) were selected randomly. Hence, 800 households were surveyed from six villages from Doyogena and 25 villages from Basona sites. The activity was conducted between 21 December 2020 to 05 January 2021 at Doyogena and between February 01 - 16, 2021 at Basona climate-smart landscapes. Twelve enumerators for Doyogena and fifteen for Basona sites were selected, trained for three days, and performed pre-testing with 8 – 10 farmers before data collection. At Doyogena, a portfolio of eleven promising CSA options was evaluated, namely, (i) terraces coupled with Desho grass (Pennisetum pedicellatum); (ii) controlled grazing; (iii) improved wheat seeds (high yielding, disease-resistant & early maturing); (iv) improved bean seeds (high yielding); (v) improved potato seeds (high yielding, bigger tuber size); (vi) cereal/potatolegume crop rotation (N fixing & non-N fixing); (vii) residue incorporation of wheat or barley; (viii) green manure: vetch and/or lupin during the off-season (N fixing in time); (ix) improved breeds for small ruminants; (x) agroforestry (woody perennials and crops); and (xi) cut and carry for animal feed. At Basona, on the other hand, the impact of seven CSA options was evaluated, namely, (i) terrace (soil bunds); (ii) terraces coupled with phalaris and tree lucerne); (iii) trenches; (iv) enclosure; (v) percolation pits; (vi) check-dams; and (vii) gully rehabilitation.